SYNTHESIS AND CHARACTERIZATION OF HYDROXYAPATITE/POLYLACTIC ACID/COLLAGEN NANOFIBROUS SCAFFOLDS FOR BONE REGENERATION - Silvia Resa Pratama; Aminatun; Ersyzario Edo Yunata; Che Azurahanim Che Abdullah (Indonesian Applied Physics Letters, 2026)
Bone defects caused by accidents, trauma, congenital abnormalities, and metabolic disorders remain a significant clinical challenge requiring effective therapeutic strategies. This study aimed to develop electrospun nanofibrous bone scaffolds based on hydroxyapatite (HA), polylactic acid (PLA), and collagen as potential candidates for bone tissue engineering by mimicking the structure of the extracellular matrix (ECM). The scaffolds were fabricated using the electrospinning technique with various HA–PLA–collagen compositions and characterized through FTIR, SEM, porosity analysis, degradation testing, mechanical property evaluation, and cytotoxicity assessment using the MTT assay. FTIR analysis indicated the absence of new chemical bond formation among the constituent materials, suggesting that the scaffold components were physically integrated. The optimal scaffold composition was obtained at an HA/PLA/collagen ratio of 50:30:20 (wt%), exhibiting an average fiber diameter of 856 ± 210 nm, porosity of 88.31%, degradation rate of 0.0238% h⁻¹, ultimate tensile strength of 1.435 ± 0.197 MPa, elastic modulus of 6.828 ± 1.037 MPa, elongation at break of 21.6%, and cell viability of 80.888%. These findings demonstrate that the HA/PLA/collagen scaffold possesses favorable physicochemical, mechanical, and biological properties, highlighting its potential as a bone scaffold for supporting and accelerating the bone remodeling process.